EXAMINING THE IMPACT OF BLOCKCHAIN TECHNOLOGY ON FINANCIAL REPORTING AND AUDITING PRACTICES - Zaenal Aripin; Ricky Agusiady; Ijang Faisal (Organisasi Kreatif Indonesia Emas, 2024)
Background: Blockchain technology is revolutionizing industries worldwide, particularly in the realm of financial reporting and auditing. Its decentralized and immutable nature has the potential to address longstanding challenges such as data integrity, fraud prevention, and real-time reporting. Aims: This study aims to explore how blockchain technology influences the transparency, accuracy, and efficiency of financial reporting and auditing practices. Research Method: The research employs a qualitative methodology, combining a comprehensive literature review with case studies from industries implementing blockchain in financial operations. Results and Conclusion: Findings reveal that blockchain enhances transparency and reduces errors in financial reporting while introducing new complexities in auditing practices, such as the need for technical expertise. The technology fosters trust through immutable records but requires regulatory frameworks to maximize its potential. Contribution: This study contributes to the growing discourse on blockchain by offering insights into its practical applications in financial reporting and auditing, along with recommendations for future integration strategies.